Adaptive Interpretation of Creatio ex Nihilo in Chaoxingxueyao: Based on the Translation of Summa Theologiae I, Q45, A1 - DENG, Zizhuo (Journal of Research for Christianity in China (JRCC), 2025)
This article explores the adaptive interpretation of creatio ex nihilo by Ludovico Buglio in his translation of St. Thomas Aquinas’ Summa Theologiae I, Q45, A1 (corresponding to ChaoXingXueYao, CXXX, Section I.3, Chapter 10.2.1). By analyzing Buglio’s textual structural adaptations and terminological choices, this study highlights his strategies for bridging Western theological concepts with Chinese cultural frameworks. The primary findings reveal that Buglio employs the Confucian term HuaCheng (化成) to translate creatio and creare, emphasizing the dynamic process of creation while adjusting the content’s organization in accordance with Ming-Qing literary conventions. His translation prioritizes readability for Chinese audiences, striking a balance between fidelity to Aquinas’s arguments and cultural adaptation. Furthermore, Buglio’s work exemplifies the early Jesuits’ efforts to negotiate theological terminology across cultural boundaries, striving to construct “equivalence relations” between Latin-Christian and Chinese philosophical terms amidst linguistic and philosophical tensions. These “equivalence relations” not only facilitated the dissemination of Christian theology in China but also provide methodological insights for the development of Sino-Christian theology in terms of translation and hermeneutics.